Nanoparticle-stabilized CO2 foam for waterflooded residual oil recovery. (15th December 2018) - Fu, Chunkai; Yu, Jianjia; Liu, Ning
Abstract: This paper presents a series of studies of nanoparticle-stabilized CO2 -foam for waterflooded residual oil recovery. A stable CO2 foam was generated as CO2 /nanosilica dispersion flowed through a porous media. The generated CO2 foam could reduce CO2 mobility and improve CO2 sweep efficiency in CO2 flooding. The particle-stabilized CO2 foam has also been observed to improve residual oil recovery after waterflooding. Effects of pressure and temperature on the performance of the CO2 foam in residual oil recovery were investigated. The results indicated that the residual oil recovery (percentage of waterflooded residual oil) by CO2 /nanosilica flooding increased from 64.9% to 75.8% when the pressure was increased from 1200 psi to 2500 psi. When temperature increased from 25 °C to 60 °C, the residual oil recovery by CO2 /nanosilica flooding decreased from 62.6% to 52.1%.